Prevalence and antimicrobial susceptibility pattern of methicillin-resistant Staphylococcus aureus (MRSA) in AL-Yarmook teaching hospital-Baghdad - Baydaa Hameed Abdullah (College of Pharmacy / Mustansiriyah University, 2013)
Nosocomial infection is a major problem in the world today. Methicillin- resistant Staphylococcus aureus (MRSA) strains, usually resistant to several antibiotics and also intrinsic resistance to ß- lactam antibiotics, shows a particular ability to spread in hospitals and now present in most of the countries. The present study was carried out to investigate the prevalence of MRSA and their rate of resistance to different antistaphylococcal antibiotics. Between Decembers 2009and April 2011, the clinical specimens submitted at the microbiology laboratory were processed and all Staphylococcus aureus (S. aureus) isolates were included in this study. All isolates were identified morphologically and biochemically by standard laboratory procedures and antibiotic susceptibility pattern including oxacillin was determined by modified Kirby Bauer disc diffusion method. Out of a total of 337 Staphylococcus aureus strains isolated from various clinical samples, 140(41.54%) were found to be Methicillin- resistant. Among MRSA isolates, 86(46.99%) were from different inpatient departments, whereas, 54 (35.06%) of the isolates were from outpatients. All MRSA were resistant to penicillin. About 70% of the MRSA strains were resistant to cephalexin, ciprofloxacin and cloxacillin ,while less than 10% of them were resistant to amikacin and tetracycline. Many MRSA strains were multidrug resistant. However, no strains were resistant to vancomycin. This report showed a high prevalence of MRSA in Al-Yarmook hospital. To reduce the prevalence of MRSA, regular surveillance of hospital acquired infection and isolation is the need of the hour.